2022
DOI: 10.1038/s41598-022-16677-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metformin on the survival of colorectal cancer patients with type 2 diabetes mellitus

Abstract: Evidence from previous studies suggests a protective effect of metformin in patients with colorectal cancer (CRC). The aim of this study was to examine the associations between metformin use and overall survival (OS) and disease-free survival (DFS) in CRC patients with type 2 diabetes mellitus (DM). We retrospectively included patients who underwent surgery for CRC at Limoges’ University Hospital between 2005 and 2019 and diagnosed with type 2 DM. Data on the characteristics of patients, CRC, comorbidities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Moreover, while lowering systemic glucose levels and improving secondary hyperinsulinemia, metformin prevents the latter effects on tumor growth and progression. However, its antineoplastic effect in CRC is quite controversial [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, while lowering systemic glucose levels and improving secondary hyperinsulinemia, metformin prevents the latter effects on tumor growth and progression. However, its antineoplastic effect in CRC is quite controversial [9].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hyperglycemia enhances resistance to 5-fluorouracil-induced apoptosis. Interestingly, various studies have shown a protective effect of metformin against cancer [9]. Metformin is an antidiabetic drug that decreases insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, metformin, which is recognized to treat T2DM, was shown that to have antitumor effects. In colorectal cancer (CRC), the use of metformin may improve disease-free survival and overall survival in CRC patients with T2DM [ 12 ]. In bladder cancer cells, metformin improves the antitumor effect of Olaparib through the STAT3/C-MYC pathway [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metformin has been associated with decreased risk of CRC in diabetic patients and prognosis improvement in CRC patients with diabetes (162). For instance, Tarhini et al (2020) showed that the use of metformin in patients with both CRC and T2D is associated with improved overall survival (adjusted hazard ratios [aHR] = 0.45, 95% CI = 0.21 -0.96) and disease-free survival (aHR = 0.31; 95% CI = 0.18 -0.54) (163). Furthermore, metformin can be considered as a senolytic drug: metformin treatment has been associated with increased tumour cell apoptosis and inhibition of SASP secretion Potential combination therapies for colorectal cancer.…”
Section: Future Directionsmentioning
confidence: 99%